1m+9=12m-8m+21

Simple and best practice solution for 1m+9=12m-8m+21 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1m+9=12m-8m+21 equation:


Simplifying
1m + 9 = 12m + -8m + 21

Reorder the terms:
9 + 1m = 12m + -8m + 21

Reorder the terms:
9 + 1m = 21 + 12m + -8m

Combine like terms: 12m + -8m = 4m
9 + 1m = 21 + 4m

Solving
9 + 1m = 21 + 4m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-4m' to each side of the equation.
9 + 1m + -4m = 21 + 4m + -4m

Combine like terms: 1m + -4m = -3m
9 + -3m = 21 + 4m + -4m

Combine like terms: 4m + -4m = 0
9 + -3m = 21 + 0
9 + -3m = 21

Add '-9' to each side of the equation.
9 + -9 + -3m = 21 + -9

Combine like terms: 9 + -9 = 0
0 + -3m = 21 + -9
-3m = 21 + -9

Combine like terms: 21 + -9 = 12
-3m = 12

Divide each side by '-3'.
m = -4

Simplifying
m = -4

See similar equations:

| 3x+26+6x+5=180 | | 4(y+5)+y=3(y+4)+6 | | x=1/2a*t^2 | | 52+x=65 | | 5/9x3/10 | | 24/1 | | 3x+26+6x+5=360 | | 4.3=x+3 | | 6x-3+2x=5x+9 | | X+29=48 | | 62.1=(20+.5x)+.15(20+.5x) | | M+9=12m-8m+21 | | 24-3w=7w+64 | | 2(-2b+5)-5b=-20+6b | | -(-2w-31)=30 | | -9(4x-2)=108-16 | | (a^3-2a^2)-(3a^2-4a^2)= | | 100000=x-.08x-260000 | | (X-2)-2(x-1)=(x+1)-(x-6) | | 46=47+1x | | cos(3x)=10x^2 | | 1260/m=20 | | 1260/m=20 | | 7x+5=8-x | | 2x+0.2=x-3 | | 80h-2=15 | | 2(x-6)=7x | | 80h-2= | | 12=z-5/3 | | 10a-3a=8+8a | | 2x+1=81 | | 12=z-5/4 |

Equations solver categories